Preclinical toxicity study of Datura metel L. based Unani formulation Habb-e-Zeequn Nafas used in the treatment of Asthma - Nargish Firdaus; Uzma Viquar; Gulam Mohammed Husain; Mohammad Zakir (Elsevier, 2022)
Background: Habb-e-Zeequn Nafas (HZN) is a traditional multi-ingredient Unani formulation that has been used to treat bronchial asthma. Datura metel L. is an ingredient in this formulation that has toxic tropane alkaloids. Despite its favorable use, no investigations on its toxicity potential have been published. Methodology: The acute and sub-acute toxicity studies were carried out following OECD Guidelines 425 and 407, respectively. The acute toxicity study was carried out at the dose of 170, 550, and 2000 mg/kg bw/day. The dose levels used in the sub-acute toxicity research were 11, 55, and 110 mg/kg bw/day. Toxicity, clinical symptoms, body weight, and feed consumption were recorded. Results: In comparison to control animals, there were no significant variations in body weight increase, feed consumption, hematological, or clinical biochemistry in HZN-treated animals. There were no significant differences in gross pathological findings between the control and drug-treated animals. A few histological alterations were found in the control and HZN-treated animals. Conclusions: Except for few histological abnormalities in the liver in the high-dose HZN group, as well as in the vehicle and satellite control groups, no treatment-related toxicologically significant alterations were identified up to the 2000 mg/kg b.w. .